Hybrid perovskites for photovoltaics: charge-carrier recombination, diffusion, and radiative efficiencies - Johnston, M; Herz, L (American Chemical Society, 2016)
Photovoltaic (PV) devices that harvest the energy provided by the sun have great potential as renewable energy sources, yet uptake has been hampered by the increased cost of solar electricity compared with fossil fuels. Hybrid metal halide perovskites have recently emerged as low-cost active materials in PV cells with power conversion efficiencies now exceeding 20%. Rapid progress has been achieved over only a few years through improvements in materials processing and device design. In addition, hybrid perovskites appear to be good light emitters under certain conditions, raising the prospect of applications in low-cost light-emitting diodes and lasers. Further optimization of such hybrid perovskite devices now needs to be supported by a better understanding of how light is converted into electrical currents and vice versa. This Account provides an overview of charge-carrier recombination and mobility mechanisms encountered in such materials. Optical-pump-terahertz-probe (OPTP) photoconductivity spectroscopy is an ideal tool here, because it allows the dynamics of mobile charge carriers inside the perovskite to be monitored following excitation with a short laser pulse whose photon energy falls into the range of the solar spectrum. We first review our insights gained from transient OPTP and photoluminescence spectroscopy on the mechanisms dominating charge-carrier recombination in these materials. We discuss that mono-molecular charge-recombination predominantly originates from trapping of charges, with trap depths being relatively shallow (tens of millielectronvolts) for hybrid lead iodide perovskites. Bimolecular recombination arises from direct band-to-band electron-hole recombination and is found to be in significant violation of the simple Langevin model. Auger recombination exhibits links with electronic band structure, in accordance with its requirement for energy and momentum conservation for all charges involved. We further discuss charge-carrier mobility values extracted from OPTP measurements and their dependence on perovskite composition and morphology. The significance of the reviewed charge-carrier recombination and mobility parameters is subsequently evaluated in terms of the charge-carrier diffusion lengths and radiative efficiencies that may be obtained for such hybrid perovskites. We particularly focus on calculating such quantities in the limit of ultra-low trap-related recombination, which has not yet been demonstrated but could be reached through further advances in material processing. We find that for thin films of hybrid lead iodide perovskites with typical charge-carrier mobilities of ∼30cm(2)/(V s), charge-carrier diffusion lengths at solar (AM1.5) irradiation are unlikely to exceed ∼10 μm even if all trap-related recombination is eliminated. We further examine the radiative efficiency for hybrid lead halide perovskite films and show that if high efficiencies are to be obtained for intermediate charge-carrier densities (n ≈ 10(14) cm(-3)) trap-related recombination lifetimes will have to be enhanced well into the microsecond range.